REVEALING THE KINDS OF GENDER INEQUALITY IN NIKI CARO’S MOVIE MULAN (2020) - Paturusi, Idham Chalid Akbar; Halim, Abd.; Nasta, Mardiyanah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to analyze the issue of gender inequality between men and women through gender roles depicted in the film Mulan 2020 by using Alice Eagly's social role theory. The findings of this study should encourage readers to perceive and comprehend feminism, gender inequality, its kinds and its impacts more clearly. Alice Eagly classifies gender inequality into two parts, namely stereotyping and subordination. This research uses a descriptive qualitative method where the main data of this research is taken from the dialog and scenes of the film Mulan (2020). The results of this study show that there are 26 data that show gender inequality which are divided into 11 data that show stereotypical expressions of masculinity, 4 data that show stereotypical expressions of femininity, and 11 data that show expressions of subordination. Society's view of the prevailing social norms has a huge impact on the roles considered suitable for each individual so that sometimes it causes inequality and this can be seen clearly in the movie Mulan.